Mengoptimalkan Kemampuan Guru Dalam Menyimpulkan Materi Pembelajaran - Feni Sulistiani Sitorus; Dorlan Naibaho (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
The teacher's ability to summarize learning material for students is important because it will provide confirmation of the material that has been studied at the meeting. In concluding the material the teacher can provide a summary of important points regarding the material studied at the meeting. Students will also find it easier to understand the meeting material. Students come to know the essence of learning. The aim of summarizing the learning material is to determine the teacher's level of success in providing explanations of the subject matter. This study covers various methods and strategies used in summarizing learning material, including training, collaboration between teachers, and the application of educational technology. Through the use of these approaches, this journal explores the results of improving the quality of teaching and learning processes in education. The results of this research underline the importance of developing teachers' abilities in summarizing learning material as one of the main factors in creating an effective learning environment. This journal provides valuable insights for educators, educational policy makers, and researchers to continue to develop approaches that can improve teachers' abilities to summarize learning material effectively, which in turn will contribute to increasing student achievement and the overall quality of education